KAJIAN DAYA DUKUNG PERMUKIMAN DI KECAMATAN SEMARANG UTARA, KOTA SEMARANG - Farand Maulana Al Javier; Sriyono Sriyono (BRILIANT: Jurnal Riset dan Konseptual, 2026)
Rapid population growth and urbanization in Semarang City, particularly in the Semarang Utara District, have placed significant pressure on the region's carrying capacity, especially in fulfilling the need for adequate housing. This study aims to analyze the residential carrying capacity in Semarang Utara District using a spatial quantitative approach through the Building Coverage Ratio (BCR) method. BCR is employed to assess the extent of land development and the availability of open space as indicators of sustainable residential environments. Data were obtained through satellite imagery analysis, documentation from related agencies, and field observations, then processed using GIS software to calculate BCR values for each sub-district. The results show that all sub-districts in Semarang Utara have BCR values exceeding 60%, with several areas surpassing 75%, indicating a very high level of development and critical carrying capacity. This condition leads to limited open space, environmental degradation, and increased disaster risks. The study recommends ecological-based spatial planning and the provision of green open spaces to restore the area’s carrying capacity in a sustainable manner.